2017
DOI: 10.1128/aem.00137-17
|View full text |Cite
|
Sign up to set email alerts
|

Genetic (In)stability of 2,6-Dichlorobenzamide Catabolism in Aminobacter sp. Strain MSH1 Biofilms under Carbon Starvation Conditions

Abstract: Aminobacter sp. strain MSH1 grows on and mineralizes the groundwater micropollutant 2,6-dichlorobenzamide (BAM) and is of interest for BAM removal in drinking water treatment plants (DWTPs). The BAM-catabolic genes in MSH1 are located on plasmid pBAM1, carrying bbdA, which encodes the conversion of BAM to 2,6-dichlorobenzoic acid (2,6-DCBA) (BbdA ϩ phenotype), and plasmid pBAM2, carrying gene clusters encoding the conversion of 2,6-DCBA to tricarboxylic acid (TCA) cycle intermediates (Dcba ϩ phenotype). There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The mobile elements associated with these catabolic clusters seem to be unstable, and are lost from most of the PromA plasmid copies in both populations. The loss of catabolic clusters from plasmids, both in the presence and absence of other C sources than the xenobiotic compound, was shown in various studies (Takahashi et al, 2009;Changey et al, 2011;Horemans et al, 2017). In case of plasmid pADP1 from Pseudomonas huttiensis, it was observed that the loss of a 47 kbp upstream atrazine catabolic region via an ISPps1-mediated homologous recombination event led to an overall fitness increase in the host when growing on the atrazine downstream degradation product cyanuric acid.…”
Section: Discussionmentioning
confidence: 98%
“…The mobile elements associated with these catabolic clusters seem to be unstable, and are lost from most of the PromA plasmid copies in both populations. The loss of catabolic clusters from plasmids, both in the presence and absence of other C sources than the xenobiotic compound, was shown in various studies (Takahashi et al, 2009;Changey et al, 2011;Horemans et al, 2017). In case of plasmid pADP1 from Pseudomonas huttiensis, it was observed that the loss of a 47 kbp upstream atrazine catabolic region via an ISPps1-mediated homologous recombination event led to an overall fitness increase in the host when growing on the atrazine downstream degradation product cyanuric acid.…”
Section: Discussionmentioning
confidence: 98%
“…A, Section A.1). Stable catabolism of the four selected isolates, probably developed under nutrient-poor conditions during isolation (Horemans et al, 2017b), was confirmed with an 88% decrease in COD even on day 21 of the pilot experiment. The coexistence tests that gave the best combination of 4 bacteria (Suppl.…”
Section: Discussionmentioning
confidence: 63%
“…In preparing the consortium, we pursued specific aims (Fig. 1): (i) Isolation of individual strains capable of degrading a range of papermaking chemicals; to isolate bacteria with stable catabolism at low nutrient concentrations, we performed bacterial isolation under nutrient-poor conditions (Horemans et al, 2017b), (ii) construction of the most suitable inoculum; we prepared different combinations of active bacteria in synthetic and real whitewater to select the combination with the broadest repertoire of carbon source use, and (iii) upscaling the use of the prepared inoculum by applying an immobilisation strategy.…”
mentioning
confidence: 99%
“…MSH1 can mineralize 2,6‐dichlorobenzamide, a major organic pollutant in groundwater, through the metabolic pathway of chlorobenzoic acid (Horemans et al . 2017). TFNG‐AM is the product of flonicamid transformed through hydration pathway, A. faecalis CGMCC 17553 could transform flonicamid into TFNG‐AM through hydration pathway mediated by nitrilase NitA, (Yang et al .…”
Section: Discussionmentioning
confidence: 99%